FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KURANGNYA PRODUKSI ASI PADA IBU MENYUSUI DI WILAYAH KERJA PUSKESMAS LUBUK BASUNG TAHUN 2020 - Rika Armalini; Setia Nisa (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2022)
Mother's Milk (ASI) is the best natural nutrition for babies because it contains the energy and substances needed for the first six months of a baby's life. Knowledge and family support play an important role in encouraging the interest or willingness of the elderly to participate in elderly Posyandu activities. The purpose of this study was to determine the relationship between knowledge and family support with the low number of visits by the elderly to the elderly Posyandu in the Working Area of ​​the Talu Health Center in 2020. The research was conducted in April 2020. This type of research was a descriptive analytic study with a cross sectional design. The population in this study were all elderly people aged 60 to > 70 years in the working area of ​​the Talu Public Health Center, using the accidental sampling technique to obtain a sample of 30 elderly people. The data were analyzed univariately and bivariately using a computerized statistical test using SPSS Ver.17 with a significance limit of α = 0.05 and a 95% degree of confidence. The results of the univariate analysis showed that 46.7% of the elderly had low knowledge, 53.3% had good family support for the elderly and 60% visited the elderly Posyandu for the elderly. Bivariate analysis found a p value (p<0.05) meaning that there was a significant relationship between knowledge (p=0.021) and attitude (p=0.004) with visits to the elderly posyandu in the Talu Health Center area in 2020. The results of this study can be concluded that it turns out that there is a relationship between knowledge and family support with visits to the elderly posyandu. It is hoped that the role of health workers will be more active in making visits to the elderly in people's homes to find out their health conditions and provide free treatment for the elderly and not stick to the activities of the elderly Posyandu.